1999
DOI: 10.1046/j.1365-2648.1999.00901.x
|View full text |Cite
|
Sign up to set email alerts
|

Social support and antenatal clinic attendance among Thai pregnant women in Hatyai, a city in southern Thailand

Abstract: Many studies in western countries have shown that persons who have a high level of social support are likely to have better health behaviours, including use of preventive health services, than those who have low support. The present study aims to investigate the impact of level of social support among Thai pregnant women on their attendance at antenatal care (ANC) clinics. The study was conducted in Hatyai, a city in Southern Thailand, between 1990 and 1991. Relationships between various measures of the women'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Social support is an interpersonal process that is context specific (Coffman & Ray, 1999, 2002; Lackner, Goldenberg, Arrizza, & Tjosvold, 1994; Olsson, 1997; Rose, 1997) and involves the exchange of information. Information as a means to an end consists of facts, advice (Arnault, 2002; Chang & Schaller, 2000; Jirojwong et al, 1999; Laakso & Paunonen‐Ilmonen, 2002; Sandstrom, 1996), words of reassurance (Coffman & Ray, 2002; Michael & Jenkins, 2001; Sandstrom, 1996), positive affirmation (Coffman & Ray, 1999, 2002; Gilliland & Bush, 2001; Gurowka & Lightman, 1995; Simich et al, 2003), empathy (Coffman & Ray, 1999, 2002; Norbeck et al, 1991; Sandstrom, 1996; Whittemore, Rankin, Callahan, Leder, & Carroll, 2000), or similar expressions of support. Although verbal exchange of information is common, social support can also be shared nonverbally through flowers, cards (Gurowka & Lightman, 1995), eye movements, facial expressions (Makabe & Hull, 2000; Neufeld & Harrison 1995), or simply being present (Bolla et al, 1996; Bricker & Fleischer, 1993; Chan et al, 2001; Makabe & Hull, 2000; Rose, 1997).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Social support is an interpersonal process that is context specific (Coffman & Ray, 1999, 2002; Lackner, Goldenberg, Arrizza, & Tjosvold, 1994; Olsson, 1997; Rose, 1997) and involves the exchange of information. Information as a means to an end consists of facts, advice (Arnault, 2002; Chang & Schaller, 2000; Jirojwong et al, 1999; Laakso & Paunonen‐Ilmonen, 2002; Sandstrom, 1996), words of reassurance (Coffman & Ray, 2002; Michael & Jenkins, 2001; Sandstrom, 1996), positive affirmation (Coffman & Ray, 1999, 2002; Gilliland & Bush, 2001; Gurowka & Lightman, 1995; Simich et al, 2003), empathy (Coffman & Ray, 1999, 2002; Norbeck et al, 1991; Sandstrom, 1996; Whittemore, Rankin, Callahan, Leder, & Carroll, 2000), or similar expressions of support. Although verbal exchange of information is common, social support can also be shared nonverbally through flowers, cards (Gurowka & Lightman, 1995), eye movements, facial expressions (Makabe & Hull, 2000; Neufeld & Harrison 1995), or simply being present (Bolla et al, 1996; Bricker & Fleischer, 1993; Chan et al, 2001; Makabe & Hull, 2000; Rose, 1997).…”
Section: Resultsmentioning
confidence: 99%
“…Providers of social support serve as advocates by motivating (Hupcey, 2001; Jankowski et al, 1996) and empowering recipients to act on their own behalf (Coffman & Ray, 1999, 2002) and to maintain as much control as possible (Chang & Schaller, 2000; Coffman & Ray, 1999, 2002; Harrison et al, 1995). Reassurance, reinforcement, affirmation, validation, and encouragement are common advocative strategies (Chan et al, 2001; Chang & Schaller, 2000; Coffman & Ray, 1999, 2002; Duffy, 1989; Gurowka & Lightman, 1995; Jirojwong et al, 1999; Murray, 2002; Norbeck et al, 1991; Sandstrom, 1996; Simich et al, 2003; Tichon & Shapiro, 2003), which are employed in an atmosphere of unconditional positive regard and caring (Chang & Schaller, 2000; Coffman & Ray, 1999; 2002; Duffy, 1989; Hildingh et al, 1995; Sandstrom, 1996). Caring includes expressions of understanding, respect, empathy, compassion or love (Chang & Schaller, 2000; Coffman & Ray, 1999, 2002; Duffy, 1989; Hudson & Morris, 1994; Norbeck et al, 1991).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While they are often cast as one of many barriers women face to better health, husbands also emerge as positive actors. For example, in a recent study of urban Thai women, husbands were found to be the primary sources of pregnancy social support (Jirojwong et al 1999). A few recent studies explore men's attitudes and behaviours towards maternal health directly.…”
Section: Male Involvementmentioning
confidence: 98%
“…For example, in India, it was evident from the focus-group transcriptions that pressure from the family with respect to not revealing a diagnosis or not revealing the terminal nature of an illness patient was often encountered. In Thailand, because families are extended, boundary enmeshment sometimes occurs and may contribute to ethical dilemmas related to these issues 40. In Japan, an elderly person is not seen as independent, but rather as a member of the “family” and of his or her community.…”
Section: Resultsmentioning
confidence: 99%